Proyecto de ley n. 21.085 Reforma de los Artículos 28 y 60 de la Ley Nº 9342, Código Procesal Civil, del 3 de febrero del 2016 - Costa Rica. Asamblea Legislativa Autoría 46158
Reforma de los Artículos 28 y 60 de la Ley Nº 9342, Código Procesal Civil, del 3 de febrero del 2016